2007
DOI: 10.1577/t06-091.1
|View full text |Cite
|
Sign up to set email alerts
|

Littoral Fish Community Response to Smallmouth Bass Removal from an Adirondack Lake

Abstract: Large‐scale observational studies in eastern Canada and the northeastern USA have concluded that introduced littoral predators are responsible for reductions in native fish diversity and abundance. To determine whether nonnative predator removal could increase native littoral fish abundance, we removed 47,682 smallmouth bass Micropterus dolomieu from a 271‐ha Adirondack lake during a 6‐year period. Two years after removal began, habitat‐stratified snorkel surveys indicated a greater than 90% reduction in small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 36 publications
0
70
0
Order By: Relevance
“…Of the case studies examined, 16 showed evidence of compensatory recruitment (Table 3. 1). Of case studies showing signs of compensation, the increase in juvenile and overall abundance was sufficient in five cases to suggest overcompensation may have occurred (Smith et al 1996, Meyer et al 2006, Weidel et al 2007, Thuesen et al 2011, Shepard et al 2014. The majority of unsuccessful removal efforts showed evidence of compensation (Fisher's exact p < 0.001; Table 3.2), though compensation appeared to have occurred in a few efforts that resulted in the successful reduction or eradication of the target species.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Of the case studies examined, 16 showed evidence of compensatory recruitment (Table 3. 1). Of case studies showing signs of compensation, the increase in juvenile and overall abundance was sufficient in five cases to suggest overcompensation may have occurred (Smith et al 1996, Meyer et al 2006, Weidel et al 2007, Thuesen et al 2011, Shepard et al 2014. The majority of unsuccessful removal efforts showed evidence of compensation (Fisher's exact p < 0.001; Table 3.2), though compensation appeared to have occurred in a few efforts that resulted in the successful reduction or eradication of the target species.…”
Section: Resultsmentioning
confidence: 97%
“…In 5 cases studies, the increase in juvenile and overall abundance was sufficient to suggest overcompensation may have occurred (Smith et al 1996, Meyer et al 2006, Weidel et al 2007, Thuesen et al 2011, Shepard et al 2014). All removal efforts containing evidence of compensation utilized only physical methods.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations